Barrett esophagus: What a mouse model can teach us about human disease - Quante, Michael (Landes Bioscience, 2012)
The incidence of esophageal adenocarcinoma (EAC) is rapidly rising in the western world and accounts for 2% of all cancer-related deaths. The precursor lesion for EAC is Barrett esophagus (BE), which is strongly associated with gastresophageal reflux disease. A major limitation to the study of EAC has been the absence of tractable and genetically modifiable preclinical models of BE. A mouse model of BE and EAC that resembles human disease could provide novel insights into the origins and molecular pathogenesis of BE. In addition, validated animal models could help stratify BE patients given the limited predictive power of current standard endoscopic measures and clinical assessment. Here, we review the findings from recently developed mouse models of BE and EAC and their impact on clinical decision making, surveillance programs and therapeutic options. The data, taken together, suggest potential origins of BE from the gastric cardia, a role of bile acid and hypergatrinemia for carcinogenesis, a growing importance for columnar-like epithelium and a critical role for Notch signaling.